CASE SERIES: MIDGUT VOLVULUS IN TWO 5-YEAR-OLD BOYS – A TALE OF TWISTED BOWELS - Dr. Hardik Shah; Dr. Jay Jasani; Dr. Sonu Akhani; Dr. Sunil Pathak; Dr. Naiya Bhavsar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Midgut volvulus due to malrotation is a surgical emergency that, if undiagnosed, can lead to catastrophic intestinal ischemia. Although most cases are detected in neonates, delayed presentation in older children poses a diagnostic challenge because of nonspecific gastrointestinal symptoms. We report two 5-year-old boys presenting with recurrent vomiting, abdominal pain, and poor oral intake. Despite similarities in age and clinical background, the two cases demonstrated subtle variations in presentation, laboratory profile, and imaging findings. Both underwent emergency laparotomy with Ladd’s procedure and appendectomy and recovered uneventfully. This case series highlights the importance of maintaining a high index of suspicion for volvulus in school-aged children with recurrent abdominal symptoms and underscores the role of timely radiological evaluation and surgical intervention in ensuring favorable outcomes.